The importance of developing the market of medical services in an innovative economy - Rakhimova, Sadokat (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article describes the current state of the medical services market in the context of innovative economy development In addition,measures to ensure the quality, efficiency and affordability of guaranteed health services have been studied and in-depth analysis of market systems of medical services in developed countries. The study investigated many theories of economists in foreign countries, especially in analyzing the market for medical services